Indications and Yield of Pediatric Endoscopy in Bahrain: A Tertiary Center Experience - Hasan M. A. Isa; Fatema Alfayez (Hindawi Limited, 2022)
Background and Objectives. Gastrointestinal (GI) endoscopy is a medical field that has been evolving in the last decades. Innovative advances in pediatric endoscopy led to more accurate diagnosis of various GI diseases. This study aimed to assess the appropriateness of endoscopic procedures' indications and to evaluate the diagnostic and therapeutic yield of pediatric GI endoscopy, considering the limitations to access this facility. Material and Methods. Retrospective, cross-sectional, and analytical chart review was performed for children who underwent GI endoscopy at Salmaniya Medical Complex, Bahrain, from 1995 to 2020. Demographic data, endoscopic indications, and findings were collected and compared. Results. Of 1,111 patients, 1,101 (99.1%) were included in the study. 589 (53.6%) patients were males. Median age at the time of endoscopy was 8 (interquartile range 3, 11) years. 1534 endoscopies were performed (1193 upper GI endoscopies (UGIE) and 341 colonoscopies) in 1296 sessions. The mean number of endoscopies per year was 59±30.9 procedures with 81.4% reduction noted after coronavirus pandemic (P<0.0001). Ratio between UGIE to colonoscopy was 3.5 : 1. Median number of endoscopies per patient was one, ranging from one to eight procedures. 1153 (89%) sessions were diagnostic, and 143 (11.0%) were therapeutic. Main endoscopic indication was chronic abdominal pain (451 (40.9%) patients) followed by upper GI bleeding (302 (27.4%) patients). Overall positive yield was 68.1% (716/1052 procedures). Endoscopic yield varies according to the type of procedure (P=0.003). Colonoscopy alone gave a higher yield (82.6%, 38/46 procedures) compared to combined procedures (75.4%, 141/187) and UGIE alone (65.6%, 537/819). Conclusions. This study emphasizes a careful selection of the type of endoscopic procedures, based on the expected endoscopic yield, to diagnose and treat pediatric GI diseases. In patients with chronic abdominal pain, endoscopy should be reserved as a second-line tool to avoid unnecessary use of invasive procedures.